Non-Invasive Micro-Test Technology and Reciprocal Grafting Provide Direct Evidence of Contrasting Na+ Transport Strategies between Cucurbita moschata and Cucurbita maxima - Mengliang Niu; Wei Luo; Liang Luo; Shanshan Chen; Huixia Zhao; Hao Zhang; Yike Qian (Agronomy, 2023)
Cucurbita species are widely used as rootstocks for cucumber, watermelon, and other plants for the restriction of toxic Na+ transport from root to shoot. Previous studies have found distinct salt tolerance strategies between Cucurbita moschata and Cucurbita maxima; the former accumulates a large amount of Na+ in the root, while the latter accumulates Na+ in the shoot. To further study the mechanism of Na+ transport in plants, four reciprocal grafts were made between MB (C. moschata) and JHL (C. maxima), denoted as MB/MB, JHL/JHL, MB/JHL, and JHL/MB (scion/rootstock). The results showed that using MB as the rootstock effectively reduced the accumulation of Na+ in the scion. Conversely, JHL rootstock tended to transfer more Na+ to the scion. To clarify this phenomenon, the velocities of Na+ flows on the root surface, stem, and vein of grafting combinations were measured using non-invasive micro-test technology. Compared with the seedlings using JHL as rootstock, the grafted combination with MB as rootstock had a higher root Na+ efflux and lower Na+ fluxes in the stem and vein. qRT-PCR analyses revealed the critical roles of salt overly sensitive 1 and high-affinity potassium as components of the mechanism enabling Na+ exclusion from the root and Na+ unloading from the stem xylem. Compared with the seedlings using MB as rootstocks, the JHL-grafted plants showed more rapid stomatal closure and decreased transpiration rate in the first three hours after salt stress but maintained a higher level under prolonged salt treatment (120 h). The tissue tolerances of JHL and MB were assessed using the isolated leaves under NaCl to exclude the influence of the root and stem. The results showed that the salinity inflicted more serious damage to MB leaves than to JHL leaves. qRT-PCR analyses indicated that the intracellular Na+/H+ transporter in the leaf vein was involved in this process. All these findings indicated that C. moschata and C. maxima adopted different strategies for regulating Na+ transport, and grafting can be used as a tool to create more salt-tolerant plants.